Enhanced Transmission and Receiver Diversity in Orthogonal Frequency Division Multiplex Systems using Blind Channel Estimation - Vivek Kumar Gupta; Sandip Vijay (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper deals with the blind channel estimation technique in OFDM system with receiver diversity to analyze the bit error rate with respect to the number of symbols. The paper clearly brings out the advantage that is being offered by the use of Blind channel estimation technique in terms of SNR requirements. Also a comparative study has been made for the analysis of BER variation with the amount i.e. number of symbols being transmitted. The work also explores the possibility of obtaining an optimum value of number of receivers that may lead to desired BER for threshold value of SNR in an OFDM system.